Trade club for climate: A climate approach to revive multilateralism - Hubertus Bardt; Galina V. Kolev (Institut der deutschen Wirtschaft (IW), 2021)
The adoption of the Paris Agreement in December 2015 calls for concerted efforts by the international community to restrain the increase in global average temperature to well below 2êC. Trade policy has the potential to contribute substantially to curbing climate change. However, the global trade system is suffering the deepest crisis in the history of the World Trade Organization (WTO). To revive multilateralism, it is crucial to pursue a positive approach based on the commitment to a common target like climate protection and reinforced by the urgency of that target. A Trade Club for Climate (TCC) or a Sector/Industry Climate Club (SICC) are alternative ways to address both the climate crisis and the crisis of the global trading system at the same time. They should be exclusive, appealing and based on the experience of the GATT and WTO negotiations. Starting the negotiations with a smaller number of countries to achieve a large progress is more feasible than involving all current WTO member states right from the beginning. The TCC could draw on the potential of trade policy to contribute to climate protection and should be an attempt to liberalise trade with environmental and climate goods and services. A SICC could focus on the main producing countries of specific industries, which would make negotiations about minimum levels of carbon prices more feasible. The discussion on the trade-climate nexus shows that there are several measures that can be taken to make trade policy work for climate. Eliminating tariffs and reducing non-tariff barriers on goods for climate protection, product labelling, green procurement and carbon border adjustment are only a few of them. The change of political power in the USA, the recent trade policy review in the EU and the increasing commitment of many other countries worldwide show that there cannot be a better time to initiate a TCC or SICCs for specific industries and launch negotiations.
Keywords: F13; F18; Q54; 330